Epicardial Interventions: Impact of Liposomal Bupivacaine on Postprocedural Management (The EPI-LIBRE Study). (July 2020) - Sharma, Sharan Prakash; Turagam, Mohit K.; Mohanty, Sanghamitra; Di Biase, Luigi; Burkhardt, David; Horton, Rodney; Natale, Andrea; Lakkireddy, Dhanunjaya
Abstract : Background: Electrophysiological procedures such as epicardial ventricular tachycardia ablation and Lariat left atrial appendage ligation that involve the epicardial space are typically associated with significant postoperative pain due to mechanical irritation and associated inflammation. There is an unmet need for an effective pain management strategy in this group of patients. We studied how this impacts patient comfort and duration of hospitalization and other associated comorbidities related to pericardial access. Methods: This is a multicenter retrospective study including 104 patients who underwent epicardial ventricular tachycardia ablation and Lariat left atrial appendage exclusion. We compared 53 patients who received postprocedural intrapericardial liposomal bupivacaine (LB)+oral colchicine (LB group) and 51 patients who received colchicine alone (non-LB group) between January 2015 and March 2018. Results: LB was associated with significant lowering of median pain scale at 6 hours (1.0 [0–2.0] versus 8.0 [6.0–8.0], P <0.001), 12 hours (1.0 [1.0–2.0] versus 6.0 [5.0–6.0], P <0.001), and up to 48 hours postprocedure. Incidence of acute severe pericarditis delayed pericardial effusion and gastrointestinal adverse effects were similar in both groups. Median length of stay was significantly lower in LB group (2.0 versus 3.0; adjusted linear coefficient −1 [CI −1.3 to −0.6], P <0.001). Subgroup analysis demonstrated similar favorable outcomes in both Lariat and epicardial ventricular tachycardia ablation groups. Conclusions: Addition of intrapericardial postprocedural LB to oral colchicine in patients undergoing epicardial access during ventricular tachycardia ablation or Lariat procedure is associated with significantly decreased numeric pain score up to 48 hours compared with colchicine alone. It is also associated with significantly shorter length of hospital stay without an increase in the risk of adverse events.